2021
DOI: 10.1088/1752-7163/ac0414
|View full text |Cite
|
Sign up to set email alerts
|

RT-PCR diagnosis of COVID-19 from exhaled breath condensate: a clinical study

Abstract: Current diagnostic testing for coronavirus disease 2019 (COVID-19) is based on detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in nasopharyngeal swab samples by reverse transcription polymerase chain reaction (RT-PCR). However, this test is associated with increased risks of viral dissemination and environmental contamination and shows relatively low sensitivity, attributable to technical deficiencies in the sampling method. Given that COVID-19 is transmitted via exhaled aerosols and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 22 publications
1
49
0
Order By: Relevance
“…It is not known whether aerosols that permeate through non-woven masks with 99% VFE can contain SARS-CoV-2 RNA. Several studies have demonstrated that expired breath contains SARS-CoV-2 RNA or antigen [11][12][13][14][15][16]. Ours is the first study to detect SARS-CoV-2 RNA in expired breath filtered with a non-woven mask with 99% VFE.…”
Section: Discussionmentioning
confidence: 83%
“…It is not known whether aerosols that permeate through non-woven masks with 99% VFE can contain SARS-CoV-2 RNA. Several studies have demonstrated that expired breath contains SARS-CoV-2 RNA or antigen [11][12][13][14][15][16]. Ours is the first study to detect SARS-CoV-2 RNA in expired breath filtered with a non-woven mask with 99% VFE.…”
Section: Discussionmentioning
confidence: 83%
“…Thus, in contrast to the MS approach, the variability in the CE-DFCS data measured for different research subjects is entirely preserved by the DS approach. This suggests the superior prediction performance achieved by the DS approach in the COVID-19 diagnosis can be attributed to the presence of unresolved molecules and potentially even the coron-avirus itself 21 . This discussion also highlights a key reason for the powerful capability of CE-DFCS for breath analysis: its high detection sensitivity to both resolved and unresolved molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Another future endeavor is to correlate breath analysis data with viral loads quantified by RT-PCR to give more direct interpretation of the COVID-19 infection status and establish the sensitivity limit of CE-DFCS 21 .…”
Section: Future Outlookmentioning
confidence: 99%
“…More recently, the SARS-CoV-2 pandemic has substantially renewed the interest towards the potential referral to EBC as diagnostic matrix for viral pathogens, and particularly for SARS-CoV-2 [ 4 , 13 , 14 , 15 , 16 , 17 , 18 ]. For instance, a study from late 2020 has showed evidence that SARS-CoV-2 can be detected in EBC by means of RT-qPCR [ 4 , 19 ], prompting an increasing interest towards the use of alternative methods such as lateral flow assays or ELISA technologies [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies have reported highly inconsistent results [ 4 , 13 , 14 , 15 , 16 , 17 , 18 , 21 , 23 , 24 ], there is a substantial lack of evidence on the referral to EBC collection on diagnosis of COVID-19. An updated synthesis of the literature may be therefore useful to healthcare professionals involved in the research of new, non-invasive options for the diagnosis of SARS-CoV-2 infections.…”
Section: Introductionmentioning
confidence: 99%